Green Urban Areas and a Landscape and Biological Characterization Applied to a Micro-basin of the Great Metropolitan Area of Costa Rica - Romero Vargas, Marilyn; Bermúdez Rojas, Tania; Durán Apuy, Alejandro; Sánchez, Marvin Alfaro; Bonilla Soto, Sebastián (Revista Geográfica de América Central., 2022)
This article presents a landscape and biological characterization of the Bermudez basin's urban green areas (UGA), based on classification according to green spaces use criteria. Landscape attributes are quantity, average size, and total area soil coverage condition. Biological attributes are the richness of species, genus, and families, percentage of exotic and native species by UGA category. Geospatial data supplied by municipalities were used in landscape components, as well as photo interpretation and own-made cartography generation. For biological components, field surveys and expert consultation, secondary sources through exhaustive revision of scientific literature and online databases. Results show 8.95% (664.68 ha) of UGA from the micro-basin’s total area is dedicated to biodiversity conservation, river protection, and recreation, while private UGA dedicated to crops and pastures are nearly quadrupled the first ones (31.33%; 2 325,81 ha). A total of 1.029 tree, shrub, herb, and creeper species had been identified, been gardens and roads the ones with more species. Vertebrate fauna is dominated by birds, followed by reptiles, amphibians, and at last, mammals. In conclusion, UGA on the study area had shown landscape and important biological differences, including quantity, size, spatial distribution, floristic and fauna richness, and they form a green weft that provides ecosystem services to the city